Mechanical properties and finite element analysis of walnut under different cracking parts - Zhang, Hong; Shen, Liuyang; Lan, Haipeng; Li, Yong; Liu, Yang; Tang, Yurong; Li, Wen (International Journal of Agricultural and Biological Engineering, 2018)
In order to reduce mechanical damage and improve extraction quality of walnut kernel during walnut cracking, the Wen-185 walnut cultivar was selected as the research object, and the mechanical properties of walnut under different cracking parts were assessed by combining compression tests and finite element analysis (FEA) method. The compression test results showed that the relationships between rupture force and deformation of walnut were nonlinear, and the cracking process of shell mainly consisted of three stages (elastic stage, plastic stage and composite elastic-plastic stage). The best method to crack walnut was the spherical compression, and the peak value of rupture force and corresponding deformation were 211.83 N and 1.68 mm, respectively. In condition of spherical compression, the shell-breaking rate, first-grade kernel rate and whole kernel rate were (91.67±2.89)%, (88.33±2.89)%, (80.00±5.00)%, respectively. The FEA results indicated that spherical compression was also the suitable way to rupture walnut, which resulted in the obvious propagation trends of shell cracks and further a better integrity of extracting walnut kernel. Therefore, the spherical contact form between walnut and cracking parts may be considered to design the structural shape of key components of walnut cracking machines, which was consistent with the analysis of compression test results. The comparison between experiment results and FEA results showed that the established FEA model can be used to analyze the mechanical properties of walnut. The research results can provide references for the structural design and optimization of key components of cracking machines for walnut or other nut crops.Keywords: walnut, mechanical damage, compression tests, mechanical properties, finite element analysisDOI: 10.25165/j.ijabe.20181106.3309Citation: Zhang H, Shen L Y, Lan H P, Li Y, Liu Y, Tang Y R, et al. Mechanical properties and finite element analysis of walnut under different cracking parts. Int J Agric & Biol Eng, 2018; 11(6): 81–88.